Viral Advertising: Branding Effects from Consumers’ Perspectives - Jiang, Yueqing (2012)
Viral advertising is popular for its high viral transmission results online. Its increased impacts on the social media users have been noticed by the author. At the same time, viewers’ negative attitudes toward traditional advertisements become obvious which can be regarded as the phenomenon of advertisement avoidance. It arouses author’s interests to know how the viral advertising reduces the viewers’ negative emotions and its performances in branding online. This paper is going to look into the branding aspects of viral advertising and explore the branding effects from consumers’ perspective in-depth.